Applying deep learning extreme multi-label classification to the biomedical and multilingual panoramas - Neves, André Daniel Costa das (2020)
Tese de mestrado em Bioinformática e Biologia Computacional, Universidade de Lisboa, Faculdade de Ciências, 2020